2018
DOI: 10.1007/s11248-018-0058-1
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a biotinylatable Sox2 mouse model to identify Sox2 complexes in vivo

Abstract: Sox2 is a Sry-box containing family member of related transcription factors sharing homology in their DNA binding domain. Sox2 is important during different stages of development, and previously we showed that Sox2 plays an important role in branching morphogenesis and epithelial cell differentiation in lung development. The transcriptional activity of Sox2 depends on its interaction with other proteins, leading to ‘complex-specific’ DNA binding and transcriptional regulation. In this study, we generated a mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…The transcription factor SOX2 is expressed early in the developing lung and is one of the first molecular signs of epithelial cells that are committed to the proximal airway fate. To identify molecular switches that hallmark the differentiation of the proximal cell toward the different cell lineages eventually covering the upper airways, such as ciliated cells, club cells and basal cells, we generated a mouse line expressing a biotinylatable tagged SOX2 ( 26 ). An additional mouse strain ubiquitously expressing the bacterial biotin birA ligase was used to biotinylate the bioSOX2 protein in vivo ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The transcription factor SOX2 is expressed early in the developing lung and is one of the first molecular signs of epithelial cells that are committed to the proximal airway fate. To identify molecular switches that hallmark the differentiation of the proximal cell toward the different cell lineages eventually covering the upper airways, such as ciliated cells, club cells and basal cells, we generated a mouse line expressing a biotinylatable tagged SOX2 ( 26 ). An additional mouse strain ubiquitously expressing the bacterial biotin birA ligase was used to biotinylate the bioSOX2 protein in vivo ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…Comparable immunoprecipitations were performed to validate the interaction between SOX2 and CHD4 using a FLAG-tagged CHD4 and a myc-tagged SOX2 protein, indicating that SOX2 and CHD4 also interact ( Figure 3C ). The interactions between SOX2 and TCF3 or WDR5 were used as positive controls, as we previously showed that these proteins interact with SOX2 ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice were kept under standard conditions. Mouse strains bioSOX2flox (Schilders, Eenjes et al 2018) and SOX21-KO (gift of Stavros Malas) were used. Wild-type animals were C57BL/6.…”
Section: Micementioning
confidence: 99%